2018
DOI: 10.1111/ppl.12712
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone‐nitric oxide interplay in plants: The story has just begun

Abstract: Both strigolactones (SLs) and nitric oxide (NO) are regulatory signals with diverse roles during plant development and stress responses. This review aims to discuss the so far available data regarding SLs-NO interplay in plant systems. The majority of the few articles dealing with SL-NO interplay focuses on the root system and it seems that NO can be an upstream negative regulator of SL biosynthesis or an upstream positive regulator of SL signaling depending on the nutrient supply. From the so far published re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 85 publications
1
22
0
Order By: Relevance
“…These data point to NO as a potential key factor in SL-exerted opposite regulatory effects in root and shoot growth. As recently reviewed ( Kolbert 2018 ), the functional SL–NO interaction seems to be quite complex. It seems that NO positively regulates SL signaling but it does not influence either SL production or the expression of SL biosynthetic genes in rice roots ( Sun et al , 2016 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These data point to NO as a potential key factor in SL-exerted opposite regulatory effects in root and shoot growth. As recently reviewed ( Kolbert 2018 ), the functional SL–NO interaction seems to be quite complex. It seems that NO positively regulates SL signaling but it does not influence either SL production or the expression of SL biosynthetic genes in rice roots ( Sun et al , 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“…It seems that NO positively regulates SL signaling but it does not influence either SL production or the expression of SL biosynthetic genes in rice roots ( Sun et al , 2016 ). In contrast, the exogenous application of SLs induced the production of NO ( Kolbert, 2018 ; Lv et al , 2018 ), but it remains unclear whether NO actually induce the production of SLs. We found that the exogenous application of NO mildly activated the expression of MAX1 and even to a lesser extent MAX2 genes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the endogenous sources of enzymatic NO in higher plants remain a subject of debate such as it was mentioned previously, its presence and function in plant cells are clear [17]. NO performs a signaling function mainly through the PTMs, S-nitrosation, nitration, and metal nitrosylation, in order to regulate gene expression and its interaction with phytohormones [165].…”
Section: Ros and No Intermediates In Signal Transductionmentioning
confidence: 99%
“…The presence of NO in higher plants is well documented. However, how NO is enzymatically generated remains a matter of debate [16][17][18]. Up to now, two possible pathways have been recognized using as substrate either L-arginine (oxidative pathway) or nitrate/nitrite (reductive pathway) involving the contribution of a l-Arg-dependent NO synthase-like activity [19] and a nitrate reductase (NR) activity [20], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing (by the addition of GR24) or lowering (by the addition of TIS108) the optimal SL level may result in similarly inhibited growth processes. Treatment with GR24 resulted in significantly increased NO content in Arabidopsis roots (Kolbert, 2019). As for NOassociated genes, the expressions of NIA1 and NIA2 as well as GSNOR1 didn't show any relevant modification in the presence of GR24 ( Figure 6).…”
Section: The Effect Of Sl Analog and Inhibitor On Root System And No-mentioning
confidence: 95%